Protocols protocol and standard operating procedures - Vaidya, Pradeep (Journal of Institute of Medicine Nepal, 2010)
DOI: http://dx.doi.org/10.3126/jiom.v32i1.3991 Journal of Institute of Medicine, April, 2010; 32:1 pp.1